Mengintegrasikan Pendidikan Multikultural dalam Upaya Resolusi Konflik Etnis - Hadi, Hairul; Suprapto, Suprapto; Djuita, Warni; Muhtar, Fathurrahman (Jurnal Ilmiah Profesi Pendidikan, 2024)
This research elucidates the crucial role of education in addressing ethnic conflicts through the integration of a multicultural approach into the curriculum and learning processes. It is a literature review analyzing scholarly articles, books, and previous research related to efforts to integrate multicultural education for achieving ethnic conflict resolution. The findings reveal several key aspects: cultural identity awareness, inclusive learning, intercultural dialogue, and education for social justice. Firstly, multicultural education aids in understanding and appreciating cultural identities, reducing ethnic stereotypes. Secondly, inclusive curriculum ensures equal representation for various ethnic groups. Thirdly, intercultural dialogue promotes communication and understanding among ethnic groups. Fourthly, multicultural education aims to create a fair and equal environment, minimizing inequalities that may trigger conflicts. In conclusion, integrating multicultural education into ethnic conflict resolution is vital for creating a harmonious and peaceful society. The significance of cultural identity awareness, inclusive learning, intercultural dialogue, and social justice underscores the essential steps toward achieving these goals. Implementing this approach in the education system can positively contribute to reducing ethnic conflicts and promoting peace at the local, national, and global levels.